Investigating the Changes in the Nature of Tropical Cyclones Due to Climate Change - Mehriar Ali Mohammadi; Mohammad Pakhireh Zan; Saeedeh Kharazmi (Nīvār)
This article aims to investigate the effects of climate change on tropical cyclones. The present study has been carried out by using and examining the available library resources. The results show that ocean surface warming leads to more intense tropical storms. On the other hand, with the rise of the ocean water level, the destructive power of storms in coastal areas will increase. The rise of the sea level itself is caused by climate change. On the other hand, the proportion of very intense tropical cyclones (Category 4 and 5) is projected to increase, even though most climate model studies predict that the total number of tropical cyclones per year will decrease or remain nearly constant. Also, models predict that as the Earth warms in the coming decades, some regions will experience an increase in the rate of intensification, a poleward shift of the geographic latitude of the maximum intensity, or a decrease in tropical cyclone forward motion. Keywords: Tropical Cyclone, Climate Change, Foresight